2011
DOI: 10.1128/aem.01599-10
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Killing by Dry Metallic Copper Surfaces

Abstract: Metallic copper surfaces rapidly and efficiently kill bacteria. Cells exposed to copper surfaces accumulated large amounts of copper ions, and this copper uptake was faster from dry copper than from moist copper. Cells suffered extensive membrane damage within minutes of exposure to dry copper. Further, cells removed from copper showed loss of cell integrity. Acute contact with metallic copper surfaces did not result in increased mutation rates or DNA lesions. These findings are important first steps for revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
372
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 457 publications
(399 citation statements)
references
References 40 publications
22
372
2
3
Order By: Relevance
“…Fig. 5, traces (1), (2) show similar bacterial inactivation kinetics under light doses of 50 mW/cm 2 and 70 mW/cm 2 . This suggests a saturation effect by the bacterial culture for the incident photons.…”
Section: Local Ph-changes and Surface Potential Evolution In The Darkmentioning
confidence: 63%
See 2 more Smart Citations
“…Fig. 5, traces (1), (2) show similar bacterial inactivation kinetics under light doses of 50 mW/cm 2 and 70 mW/cm 2 . This suggests a saturation effect by the bacterial culture for the incident photons.…”
Section: Local Ph-changes and Surface Potential Evolution In The Darkmentioning
confidence: 63%
“…Preparation of binary oxides films by sputtering, quantitative analysis of the film content by X-ray fluorescence (XRF) and CO 2 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu-ions reveal efficient antimicrobial activity degrading membrane/LPS layers [1,14,17,18,23,56]. Espirito-Santo [21,22] and Lemire et al [57] have recently reported bacterial inactivation on Cu surfaces. Results presented in Fig.…”
Section: Bacterial Inactivation Kinetics In the Dark And Under Light mentioning
confidence: 99%
“…Recent results have reported by Pillai et al [18][19][20], Espirito-Santo et al [21,22], Borkow et al [23,24], Liu et al [25], Dionysiou et al [26,27] and Bahneman et al [28] for disinfection on surfaces energized by solar irradiation. Because of its unique electronic structure, magnetic and optical properties, Cu 2 O has been used in catalysis/photocatalysis [29] and in solar energy conversion into electrical energy [30][31][32].…”
Section: Introductionmentioning
confidence: 98%